Coastal dynamics of uplifted and emerged late Pleistocene near-shore coral patch reefs at fins (eastern coastal Oman, Gulf of Oman). (February 2018) - Mattern, Frank; Moraetis, Daniel; Abbasi, Iftikhar; Al Shukaili, Bushra; Scharf, Andreas; Claereboudt, Michel; Looker, Elayne; Al Haddabi, Nihal; Pracejus, Bernhard
Abstract: We investigated two coral patch reefs of probably Weichselian age (Wyns et al., 1992a) which have been uplifted above sea-level in the coastal setting of uplifted marine terraces adjacent to the Oman Mountains. Uplift is also manifested in raised beach conglomerates and a wave-cut notch. We document some of the main reef features in the apprehension that building/development will preclude the study of the reefs in the near future. The reefs formed above a hardground of bioclastic limestone (mudstone to wackestone), characterized by intense bioerosion and red algae. The red algae may occur so plentiful to form (very localized) bafflestones. The diagenetic history of the rocks includes a transition from a marine environment (first cement) to meteoric conditions (dissolution and second cement). The reefs are 1.5 m thick and display planar as well as gently ocean-dipping reef tops, suggesting exposure to the wave-cut activity and, thus, shallow and nearshore deposition. The reefs are dominated by one coral species, identified as Cyphastrea serailia . On the protected side of the reefs the corals developed wavy and columnar growth forms while on the ocean facing side irregularly shaped exoskeletons developed. Our GPS-based topographic survey revealed an elevation of the two reefs of 21.5 m ± 0.06 m above sea-level. Taking into account (1) the global Holocene sea-level rise of 120 m ± 20 m (Pirazzoli and Pluet, 1991), (2) formation of the reefs slightly below sea-level (∼1.5 m) as well as (3) their present position above sea-level, we quantify the total upward transfer of the reefs to be 143 m and the average uplift rate to be 6.8 or 4.6 mm/yr depending on the correct age (either ∼21, 000 or ∼31, 000 yr B.P.). As the causes of uplift we mainly consider isostatic rebound following the late Cretaceous formation of the Oman Mountains (Yuan et al., 2016). The terrace development went through the following stages: (1) The patch reefs formed in shallow water. (2) Initial, gentle uplift caused abrasion of the reef tops. (3) Uplift continued and beach conglomerate 1was deposited on top of the reefs. (4) Abrasion continued, creating an abrasion platform. Uplift and creation of borings in platform required time and an interval of relatively slow uplift and tectonically and climatically stable conditions. (5) Uplift took place, and a wave-cut notch formed below the reefs. (6) Notch formation, including the borings into the notch, required time and stable conditions and was followed by deposition of beach conglomerate 2. (7) Finally, emergence/exposure of the notch and conglomerate 2 above sea-level ensued due to pronounced uplift, possibly associated with faulting and earthquakes. Formation of the reefs and the abrasion platform can be correlated with MIS 3 (Marine Isotope Stage 3) and notch formation with MIS 1. Highlights: Two Weichselian coral patch reefs were uplifted above sea-level at coastal Fins. A GPS-based survey revealed a reef elevation of 21.5 m ± 0.06 m above sea-level. The total reef uplift amounts to 143 m. The uplift rate is 6.8 or 4.6 mm/yr depending on the correct age of the reefs. Formation of the reefs can be correlated with the Marine Isotope Stage 3.